Kedudukan Hak Konstitusional Warga Negara Terkait Gagasan Calon Perseorangan/Independen Di Dalam Pemilihan Umum Presiden dan Wakil Presiden - Siti Fariza (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractGeneral elections are held with the aim of electing people's representatives, as well as to form a government that is democratic, strong, and obtains popular support. Besides aiming to realize national goals as the 1945 Constitution. In general elections there are candidates who are not proposed by political parties or a combination of political parties called individual candidates or independent candidates. This research uses normative juridical and library research by evaluating the laws and regulations, books, journals, and related internet sources. The results of the study showed that there were still no legitimate or independent candidates being approved, thus indicating the blockage of citizens' constitutional rights to be elected in a general election.Keywords: General Election, Presidential and Vice-Presidential Candidates, Individual or Independent Candidates